Dispersion characteristics of a helically cladded step-index optical fiber: An analytical study - Singh U.N.; Singh O.N., II; Khastgir P.; Dey K.K. (My University, 2025)
A new type of step-index optical fiber, the helically cladded fiber (HCF), in which a conducting sheath helix is introduced at the core-cladding interface boundary, is proposed. By application of the appropriate sheathhelix boundary condition at the core-cladding interface, the modal characteristic equation is determined. The dispersion curves are also obtained. Analysis of the modal characteristic equation and dispersion curves reveals that only hybrid modes are supported, and the lowest-order mode is HE01. The pitch angle of the helix has no effect on the cutoff condition. Its effect is more pronounced in the case of the first odd modes. One retrieves the modal characteristics of the step-index fiber by setting the pitch angle equal to zero. Further, a fact of technical importance emerges: that the HCF behaves as a monomode guide for a comparatively large core radius. © 1995 Optical Society of America.